Unveiling Employee Turnover Phenomena in South East Asia’s Largest Population - Utami, Ami Fitri; Nur Suci, Rumondang Puji; Shakira, Aisyah (Fakultas Ekonomi dan Bisnis, Telkom University., 2023)
Generation Y is known as a generation that grew up with technological advances, creating more dynamic, creative, and career development-oriented employees. However, they are also known as having a low level of loyalty. It is caused because Gen Y tends to have high turnover intentions. Companies need to understand the values of Gen Y to develop management strategies so employees can be maintained. Employees who feel their contribution is valued by their organization will have a high commitment to the company. It also happens when they feel the supervisors show concern for them. This study aims to identify the role of person-organization fit, perceived organizational support, and perceived supervisor support on the turnover intention of Jakarta’s Gen Y employees. The analytical method is quantitative, with 428 samples. The results of this study shall be considered for companies to determine the exact strategies for Gen Y employees. Keywords— Generation Y; Turnover Intention; Person-Organization Fit; Perceived Organizational Support; Perceived Supervisor Support